Utilising laguerre function in predictive functional control to ensure prediction consistency - Abdullah, Muhammad; Rossiter, John Anthony (IEEE, 2016)
This work proposes the use of Laguerre function in Predictive Functional Control (PFC) to produce well-posed decision making. The constant control input assumption of a classical PFC is replaced with the Laguerre polynomial and the steady state input of a system. With this slight modification, better consistency between model predictions and an actual system behaviour is achieved. In addition, the effectiveness of desired closed-loop time constant as PFC tuning parameter becomes more significant. The coding and tuning processes of the proposed approach are very straightforward and in line with the key selling points of PFC.